Writing Short Stories Using Twitter as a Media for Student’s Writing Skills - Indriani, Emma Dwi; Romadhon, Latifah Rakhma; Setiawan, Kunrat Nur (Universitas Islam Negeri Raden Intan Lampung, 2020)
The purpose of this research is to find out the improvement of students writing a short story about their most memorable experiences using Twitter as their writing media. Samples were students of class IX SMP N 3 Tangerang with a total of 30 students. According to Hadi, M, S. (2019), to solve problems and improve the quality of learning, researchers use Classroom Action Research to reduce misconceptions. Researchers conducted 1 Pre-Test session and 2 Post-Test sessions. Moreover, researchers collected data in this study by using Qualitative data from the description of students writing a story using Twitter. The results of the study showed that using social media Twitter as written media students can improve students' ability to write English and increase students' experience in conveying their expressions with written stories. From the results of the Pre-Test session, there were only 2 students who scored between 60-64. Furthermore, 28 students get grades below 60. While during the Post-test 1 session, there was an increase in students with a total of 2 students getting grades above 70. Then during the Post-Test 2 session, the increase in students improved with the achievement of student grades the highest is 80 and the lowest is 65.